Pengaruh Blended learning terhadap Hasil Belajar Siswa Kelas X pada Mata Pelajaran Bahasa Inggris (Studi Kasus pada SMK Barunawati Jakarta Utara) - Wahyu Utama (Neolectura, 2021)
This study aims to determine the effect of blended learning on student learning outcomes in English subjects at SMK Barunawati, North Jakarta. The research method used to analyze is a quantitative calculation method with an associative approach (correlation), which is to determine the influence between blended learning competencies and student learning outcomes. Data collection methods used are observation and questionnaires (questionnaires). Samples were taken as many as 76 students of class X. Based on the results of observations made on student grades, it showed that there was an increase in the average score of students in semester 1 from 81.47 to 84 so it can be ascertained that blended learning affects student learning outcomes. And based on the results of the calculation of the correlation coefficient r = 0.743, which means blended learning has a strong enough relationship to student learning outcomes. While the coefficient of determination is 50.20% so it can be concluded that blended learning affects student learning outcomes by 50.20% and the remaining 49.80% is influenced by other factors. Furthermore, the hypothesis test was obtained that thitung>ttabel was 9,550 > 1,665, so Ho was rejected and Ha was accepted, so it can be concluded that there is a significant influence between pedagogical competence and teacher creativity on student learning outcomes.